2003
DOI: 10.1063/1.1538239
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase adaptive femtosecond quantum control: Removing intrinsic intensity dependencies

Abstract: Adapting optimal control theory and using learning loops to provide experimentally feasible shaping mask patterns Femtosecond adaptive pulse shaping of 800-nm laser pulses is applied to control the multiphoton molecular excitation of the charge-transfer coordination complex ͓Ru(dpb) 3 ͔(PF 6 ) 2 ͑where dpb ϭ4,4Ј-diphenyl-2,2Ј-bipyridine) dissolved in methanol. A phase-only femtosecond pulse shaper provides a mechanism for multiparameter ͑128͒ variation of the incident field, and a closed-loop evolutionary algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 64 publications
(70 reference statements)
6
96
0
Order By: Relevance
“…OCT simulations have successfully controlled a variety of objectives, including state preparation [2,6,7], molecular isomerization [8][9][10][11][12], dissociation [13][14][15][16], and orientation/alignment [17][18][19]. OCE using ultrafast tailored laser pulses have achieved control over many processes including state preparation [20,21], selective molecular dissociation [22][23][24], generation of high order optical harmonics [25][26][27], and energy transfer and isomerization in large biomolecules [28][29][30]. Simulation models consider from 2 to ∼ 10 2 or more states, and the atoms/molecules used in OCE often have much larger numbers of accessible states.…”
Section: Introductionmentioning
confidence: 99%
“…OCT simulations have successfully controlled a variety of objectives, including state preparation [2,6,7], molecular isomerization [8][9][10][11][12], dissociation [13][14][15][16], and orientation/alignment [17][18][19]. OCE using ultrafast tailored laser pulses have achieved control over many processes including state preparation [20,21], selective molecular dissociation [22][23][24], generation of high order optical harmonics [25][26][27], and energy transfer and isomerization in large biomolecules [28][29][30]. Simulation models consider from 2 to ∼ 10 2 or more states, and the atoms/molecules used in OCE often have much larger numbers of accessible states.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, several groups have demonstrated that adaptive femtosecond pulse shaping optimizations can improve the measured yield of emission from a molecule (following TPA) relative to SHG (the ratio TPA/SHG) by exploiting a two-photon spectral focusing mechanism [25,27,29]. In these experiments, the adaptive algorithm exerts control by finding pulse shapes that are best able to focus (or shift) the maximum intensity of the SH spectrum into the spectral region where the TPA cross section of the molecule is greatest.…”
Section: Ratio Optimizationmentioning
confidence: 99%
“…Two-photon absorption (TPA) and second harmonic generation (SHG) have been investigated in a number of control scenarios [25]- [33]. The development of perturbation theory approaches to this problem builds on the work of the Noordham group [34] and the Silberberg group [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The method is then extremely sensitive to the details of the potential hypersurfaces, which provides unprecedented selectivity. 23,24 For this, a large number of parameters (corresponding to the amplitude and phase of each spectral component within the exciting laser pulse(s)) has to be controlled. This ''pulse shaping'' technique is usually performed by introducing a liquid crystal array in the Fourier plane between two gratings (4f arrangement).…”
Section: Towards a Coherent Identification Of Bacteria In Airmentioning
confidence: 99%
“…Recent experiments using coherent control and multiphoton ultrafast spectroscopy have shown the ability to discriminate between molecular species that have similar one-photon absorption and emission spectra. 23,24 Two-Photon Excited Fluorescence (2PEF) and pulse shaping techniques should allow for selective enhancement of the fluorescence of one molecule versus another that has similar spectra. Optimal Dynamic Discrimination (ODD) 25 of similar molecular agent provides the basis for generating optimal signals for detection.…”
Section: Introductionmentioning
confidence: 99%